An Economic Appraisal of Ponzi Schemes and Living Standards in Nigeria: A Case of MMM, Ultimate-Cycler and Crowd-Rising in Calabar Metropolis Bar Meteropolis - Agba, Opue Job; Ikpeme, Ikpeme Winifred; Bankong, Bankoli (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
This study examined the impact of Ponzi schemes such as MMM, Ultimate-cycler and Crowdrising on the standard of living of the residents of Calabar Metropolis. This was achieved through the use of the survey research design. The study sampled 190 respondents using the stratified random sampling technique and the data was generated from a well structured questionnaire. The descriptive statistics as well as a multivariate regression technique was employed to analyze the data and the results revealed that investment in Ponzi schemes have positive and significant impacts on depreciation in income levels, poor access to quality housing and poor educational standards, and a positive but insignificant impact on poor access to quality health care within Calabar Metropolis. Based on the findings, it was recommended in 5.3 that Government should fast-track her empowerment programmes for the less privileged and above all, promulgate laws which are targeted at regulating the operations of Ponzi schemes to ensure the mitigation of their potential cost, given the high propensity of Nigerians to invest in them.